Bruh how’s it gonna tell me incorrect answer when it was right
14.59
To solve, simply plug -7.1 into -Z. Since Z is negative in the equation, it will turn the Z that’s given to us into a negative. Since that Z is already negative, it will now become a positive since that’s what two negatives being multiplied make. This is what your problem will look like:
-(-7.1) + 7.49
7.1 + 7.49 = 14.59
Is 3.
3×3=9
Hope this helps!
Answer:
Joe Mama :))))))))))))))))))))))
Step-by-step explanation:
3, 6, 12,<u> 24 ,</u> <u>48 </u> <=== answer